DPP-4 inhibitors and their potential role in the management of type 2 diabetes - BARNETT, A. (International journal of clinical practice (Esher), 2006)
Summary The dipeptidyl peptidase 4 (DPP‐4) inhibitors enhance the body's own ability to control blood glucose by increasing the active levels of incretin hormones in the body. Their mechanism of action is distinct from any existing class of oral glucose‐lowering agents. They control elevated blood glucose by triggering pancreatic insulin secretion, suppressing pancreatic glucagon secretion, and signalling the liver to reduce glucose production. The leading DPP‐4 inhibitors have shown clinically significant HbA1c reductions up to 1 year of treatment and offer many potential advantages over existing diabetes therapies including a low risk of hypoglycaemia, no effect on body weight, and the potential, based on animal and in vitro studies, for the regeneration and differentiation of pancreatic β‐cells. They are efficacious as monotherapy and also in combination with commonly prescribed antidiabetic agents and are suitable for once‐daily oral dosing. Consequently, many DPP‐4 inhibitors such as vildagliptin (Galvus; LAF‐237), sitagliptin (Januvia; MK‐0431), and saxagliptin (BMS‐477118) have advanced into late‐stage human clinical trials. Search strategy and selection criteria  This review was built on a systematic MEDLINE search for publications on the subject with the key words: DPP‐4 inhibitor; vildagliptin (LAF‐237); sitagliptin (MK‐0431); saxagliptin (BMS‐477118); and type 2 diabetes; up to August 2006. Meeting s were also searched, as much of the data currently only exists in form. Take home message for clinician  The DPP‐4 inhibitors appear to have great potential for the treatment of type 2 diabetes, but time will tell if this will be realized. While they do not lower glucose to a greater extent than existing therapies, they offer many potential advantages, including the ability to achieve sustainable reductions in HbA1c with a well‐tolerated agent that has a low risk of hypoglycaemia and no weight gain, and which can be administered as a once‐daily oral dose.